Reestructuración técnico administrativa en la empresa Fumidorado S.A.S. en la ciudad de Bogotá, D.C. (2020)
In this degree work a technical-administrative restructuring proposal was made for the company Fumidorado S. A. S. in the city of Bogotá D. C., during the second semester of 2019. With the aim of improving its operation based on productivity and internal processes. Firstly, and by means of a diagnosis, the current situation of the company was precisely identified based on both external and internal information of the organization. Using the method of direct contact through primary and secondary sources, various tools for collecting information were applied, such as PESTAL analysis, and the business self-diagnosis of the Chamber of Commerce to evaluate the company through the DOFA matrix.